Always the queen : the Denise LaSalle story - LaSalle, Denise; Whiteis, David (Music in American life., 2020)
"This is the autobiography of soul and blues singer Denise LaSalle "as told to" the blues scholar David Whiteis. The book documents Ms. LaSalle's move from rural Mississippi to Chicago as a teenager, where she eventually established herself as a successful songwriter and performer in gospel and blues. She also founded several record labels and demonstrated considerable savvy as a businesswoman. In the early 1980s, realizing that her brand of emotionally resonant soul music had lost ground in the marketplace to newer forms - first disco, and then rap/hip-hop - Ms. LaSalle began to write songs and perform in the modern-day blues genre usually referred to as "soul-blues" (a term she takes credit for inventing) or "southern soul." Her songs in this genre conveyed a bold, often provocative message of womanly assertiveness and pride, including explicitly drawn demands for both sexual and financial satisfaction, that both invoked and modernized the classic blueswoman's stance of power and independence, a trope that links her directly to such legendary blues singers as Bessie Smith, Ma Rainey, and Ida Cox. Armed with this new material but still capable of pleasing long-time fans with renditions of her earlier hits, Ms. LaSalle became one of the dominant figures on the "southern soul"/"soul-blues" circuit, which was actually a newly revitalized incarnation of the old "chitlin' circuit," the network of predominantly African-American performance venues that crisscrossed the south and also extended into some northern and western urban strongholds (tracing, more or less, the geographic pattern of the early/mid-20th Century Great Migration). She remains one of the most beloved figures on that circuit, admired by listeners and fellow artists alike for her legacy and her ongoing dedication to her music and fans. LaSalle's story thus complements the overall story of blues and soul music as the cultural expression of a diasporan people who reinvented themselves to adjust to Northern life while retaining many of the cultural, religious, and social traditions with which they had grown up in the South"--